Coaching a realistic perspective - Sabock, Michael D.; Sabock,Ralph J. (Lanham, Maryland, 2011)
This book about Coaching: A Realistic Perspective is the ideal textbook for anyone entering the coaching profession, of any sport. More than detailing the duties and tasks of a coach
Keywords: Coaching (Athletics)